Destabilization of the human epigenome: consequences of foreign DNA insertions. (August 2015) - Weber, Stefanie; Hofmann, Andrea; Herms, Stefan; Hoffmann, Per; Doerfler, Walter
Aim: We previously reported changes of DNA methylation and transcription patterns in mammalian cells that carry integrated foreign DNA. Experiments were now designed to assess the epigenetic consequences of inserting a 5.6 kbp plasmid into the human genome.Methods: Differential transcription and CpG methylation patterns were compared between transgenomic and nontransgenomic cell clones by using gene chip microarray systems.Results: In 4.7% of the 28.869 gene segments analyzed, transcriptional activities were up- or downregulated in the transgenomic cell clones. Genome-wide profiling revealed differential methylation in 3791 of > 480, 000 CpG's examined in transgenomic versus nontransgenomic clones.Conclusion: The data document genome-wide effects of foreign DNA insertions on the epigenetic stability of human cells. Many fields in experimental biology and medicine employ transgenomic or otherwise genome-manipulated cells or organisms without considering the epigenetic consequences for the recipient genomes.